2022
DOI: 10.1038/s41598-022-11474-4
|View full text |Cite
|
Sign up to set email alerts
|

Establishing the transdiagnostic contextual pathways of emotional outbursts

Abstract: Emotional outbursts or temper outbursts are challenging behaviours commonly experienced by people with neurodevelopmental disorders and people who have experienced childhood adversity, which can negatively impact individuals and their families. Emotional outbursts may manifest in different situations via unique pathways distinguished by context-specific differences in the regulation and expression of emotions. Caregivers (N = 268) of young people (6–25 years) with emotional outbursts completed a bespoke caregi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(25 citation statements)
references
References 65 publications
0
24
1
Order By: Relevance
“…The eight sensory systems are visual, auditory, olfactory, gustatory, tactile, proprioceptive, vestibular, and interoception. These are highly central to understanding sensory processing in autism and a sensory integration approach would make them very relevant to investigating visual processing (27)(28)(29). Sensory processing disorder is often a comorbid symptom of ASD, but not all children with sensory processing disorder have autism.…”
Section: Introductionmentioning
confidence: 99%
“…The eight sensory systems are visual, auditory, olfactory, gustatory, tactile, proprioceptive, vestibular, and interoception. These are highly central to understanding sensory processing in autism and a sensory integration approach would make them very relevant to investigating visual processing (27)(28)(29). Sensory processing disorder is often a comorbid symptom of ASD, but not all children with sensory processing disorder have autism.…”
Section: Introductionmentioning
confidence: 99%
“…This paper forms part of a larger cross-sectional study investigating emotional outbursts in young people with neurodevelopmental disorders 10 . The current sample is a sub-sample of the wider study.…”
Section: Methodsmentioning
confidence: 99%
“…A study investigating autistic individuals’ experiences of outbursts found that during an outburst they may feel psychologically and physicaly overwhelmed due to feeling not in control of their actions, and may go on to feel further distress afterwards because of remorse for aggressive actions 9 . Despite the prevalence of emotional outbursts, and their impact on both the individual and those around them, effective interventions targeting outbursts are lacking 4 , 10 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations